Reformulation of the Epistemology of Islamic Education: Examine Noeng Muhadjir's Thoughts - Hamka (Tarbiyah Departement collaboration with AMCA, 2021)
This article shows that revelation is a barometer of the truth of science, as can be concluded from Noeng Muhadjir's thoughts. Any scientific product cannot be accepted if it is in apparent contradiction with the qat'i nash. This article is classified as qualitative research that uses a library research model. The primary data source is the works of Noeng Muhadjir, especially the article entitled,